Association of Streptococcus bovis with colorectal carcinoma - Nooria R. S. Mohammed (مجلة كلية الطب, 2010)
Background: - This study was carried out to investigate the ability of Streptococcus bovis to colonise colorectal cancer. Patients and Methods: - A total of 106 outpatients were subjected for colonscopy. Carcinoma biopsies from patients with colorectal cancer tissue from patient with polyps and normal mucosa stool and blood from all patient and controls were cultured and identified for S.bovis. Results: - The histopatholgical findings confirmed that 38 patients had colorectal carninoma, 27 patients with benign polyps and 41 with normal colonic mucosa. The faecal carriage rate of S.bovis was 15(39.5%) in patient with colorected cancer, 5(18.5%) in patients with polyp and 7(17.1%) in control. Conclusion: - Faecal colonization by Streptococcus bovis in colorectal cancer patient was higher than in control healthy people and patients with polyp.